CSC583: Artificial Intelligence Algorithms / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
The aim of this course is to introduce students to the fundamentals of key intelligent systems technologies including expert systems, neural networks, fuzzy systems, evolutionary computation and swarm intelligence. Besides that, the students will also be familiarized with the integration of intelligent systems technologies for science and engineering applications.